GOZZI, Ricardo. Educação sob ataque: resistência e luta dos educadores no Paraná. São Paulo: Campos, 2016, 192 p - Editor, REA (Revista Espaço Acadêmico, 2016)
GOZZI, Ricardo. Educação sob ataque: resistência e luta dos educadores no Paraná São Paulo: Campos, 2016, 192 p